Distributive Justice and Schumpeterian Innovative Evolution - an Axiomatic Approach in the Context of Social Cohesion - Malawski, Andrzej (Sprawiedliwość dystrybutywna i rozwój innowacyjny u Schumpetera - ujęcie aksjomatyczne w kontekście spójności społecznej, 2009)
The aim of the paper is to examine axiomatically the rules of distributive justice as a component of the broad idea of social cohesion in the context of the Schumpeterian evolution. The methodology of studying Schumpeterian evolution in the dynamic axiomatic Arrow-Debreu set-up is now extended in the two new directions, neglected before. Firstly, the relationship between the circular flow and economic development, which did not find any satisfactory solution in Schumpeter’s work, is studied. Secondly, the rules of distributive justice can be viewed as the components of a broad idea of social cohesion as defined by the Council of Europe, so that some aspects of it can be analyzed more rigorously. In particular, it turns out that the innovative Schumpeterian evolution based on the principle of creative destruction does not ruin the social structure built on the Rawlsian rules of distributive justice. Consequently, an evolutionary process of sustaining and enhancing l-justice relation as well as of improving the social cohesion in this aspect is constructed.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 73, s. 25-40